1999
DOI: 10.1164/ajrccm.159.6.9704025
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ventilator-dependent Patients to Different Levels of Pressure Support and Proportional Assist

Abstract: The ventilator's response to the patient's effort is quite different in proportional assist ventilation (PAV) and pressure support ventilation (PSV). We wished to determine whether this results in different ventilatory and breathing pattern responses to alterations in level of support and, if so, whether there are any gas exchange consequences. Fourteen patients were studied. Average elastance (E) was 22.8 (range, 14 -36) cm H2O/L and average resistance (R) was 15. 7 (range, 9-21) cm H2O/L/s. The highest PSV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
21

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 21 publications
5
70
1
21
Order By: Relevance
“…Leung et al showed that the pressure-time product of the diaphragm increased during the wasted efforts, but different from the present study, they still found a decrease in the pressure-time product when all breaths (triggered and not triggered) were considered. Work by other groups has since demonstrated that the asynchrony during PSV is due to dynamic hyperinflation (20). Our current results in rabbits of increased diaphragm energy expenditure at high levels of PSV are different from our previous study in ventilated adult patients, where increasing PSV reduced the EAdi and Pdi consistently.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Leung et al showed that the pressure-time product of the diaphragm increased during the wasted efforts, but different from the present study, they still found a decrease in the pressure-time product when all breaths (triggered and not triggered) were considered. Work by other groups has since demonstrated that the asynchrony during PSV is due to dynamic hyperinflation (20). Our current results in rabbits of increased diaphragm energy expenditure at high levels of PSV are different from our previous study in ventilated adult patients, where increasing PSV reduced the EAdi and Pdi consistently.…”
Section: Discussioncontrasting
confidence: 99%
“…As there were three to four steps tested with either mode, to allow for comparisons, the data were divided into three levels of assist in each mode (NAVAlo, NAVAmed, and NAVAhi and PSVlo, PSVmed, and PSVhi), as described by others (20). All variables were analyzed for NAVAlo, NAVAmed, NAVAhi and PSVlo, PSVmed, and PSVhi with nonparametric tests for repeated-measures analysis of variance (ANOVA) (Friedman repeated-measures ANOVA on ranks) (Sigmastat, Jandel Scientific, San Rafael, CA).…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] As with the evaluation of PAV in other settings, most of the comparisons have focused on the physiologic response when PSV is changed to PAV. In general, during invasive ventilation the change from PSV to PAV results in lower tidal volume, more rapid respiratory rate, lower peak airway pressure, and lower mean airway pressure, without significant changes in gas exchange or hemodynamics.…”
Section: Invasive Mechanical Ventilationmentioning
confidence: 99%
“…Use of an esophageal balloon, which permits determination of pleural pressure, and respiratory muscle electromyograms have been used to measure a variety of patient-ventilator interactions and to compute WOB. [5][6][7][8][9] However, these devices are not used during routine patient care, and clinicians must rely on physical examination of the patient as well as visual inspection of waveforms to assess for patient-ventilator syn-chrony and asynchrony. Visual inspection of waveforms has been shown to correlate well with esophageal-balloon readings, but is not without error.…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection of waveforms has been shown to correlate well with esophageal-balloon readings, but is not without error. 5,6 Artifacts such as cardiac oscillation may mimic asynchronies, and clinicians must learn to distinguish between these and true asynchronies. 10 There are times when clinicians standing at the bedside are unable to distinguish between asynchrony and artifact with certainty, in which case he/she has to use clinical judgment to determine optimal patient treatment.…”
Section: Introductionmentioning
confidence: 99%